Les kipov z območja zahodne in osrednje Afrike - Zajc, Anže (Les (Ljubljana), 2026)
The Slovene Ethnographic Museum (SEM) in Ljubljana, Slovenia, houses numerous collections of wooden objects from around the world. In this work we have examined nine sculptures from West and Central Africa. The goal of the research was microscopic wood identification, which is required as the sculptures are made of lesser known wood species. After the selection, we precisely examined, described and photographed the sculptures Based on their shapes, museum sources and available literature, we assigned the sculptures to specific regions of Africa. We carefully collected small samples of wood for anatomical analysis, taking care to preserve the structural integrity of the sculptures and ensure that the sampling locations remained invisible. We made permanent slides for microscopic wood identification. Using a light microscope, available literature, and anatomical characteristics, we were able to determine the following taxa: Diospyros spp., Guibourtia spp., Millettia spp., Cylicodiscus spp., Ceiba pentandra, Xylocarpus spp., Dracontomelon dao, and Balanites cf. aegyptiaca. The results of wood identification complement the documentation of the sculptures.
Keywords: anatomija lesa; identifikacija lesa; light microscope; museum artefacts; muzejski predmeti; Slovene Ethnographic Museum; Slovenski etnografski muzej; svetlobni mikroskop; tropical Africa; tropska Afrika; wood anatomy; wood identification